A one-dimensional high-order commensurate phase of tilted molecules. Issue 16 (6th April 2022) - Thomas, Anthony; Leoni, Thomas; Siri, Olivier; Becker, Conrad; Unzog, Martin; Kern, Christian; Puschnig, Peter; Zeppenfeld, Peter
Abstract : We report on the formation of a quasi-1D high-order commensurate (HOC) structure of dihydro-tetraazapentacene (DHTAP) molecules on a Cu(110)–(2 × 1)O surface and its stabilization through internal degrees of freedoms, namely the molecular tilt. Abstract : We report on the formation of a high-order commensurate (HOC) structure of 5, 14-dihydro-5, 7, 12, 14-tetraazapentacene (DHTAP) molecules on the highly corrugated Cu(110)–(2 × 1)O surface. Scanning tunnelling microscopy shows that the DHTAP molecules form a periodic uniaxial arrangement in which groups of seven molecules are distributed over exactly nine substrate lattice spacings along the [1̄10] direction. DFT-calculations reveal that this peculiar arrangement is associated with different tilting of the seven DHTAP molecules within the quasi one-dimensional HOC unit cell. The orientational degree of freedom thus adds a new parameter, which can efficiently stabilize complex molecular structures on corrugated surfaces.